(untitled) (Physical Education, Health and Social Sciences, 2025)
Objective: To develop a standard scale of assertiveness for adults in Urdu language. Study Design: Cross-sectional study. Place and Duration of Study: Department of Psychology, University of Gujrat, Gujrat Pakistan, from January to October 2019. Methodology: This research was accompanied on the adults, age range of 19 to 60. An item pool of 132 items was developed after the in-depth literature review. Moreover, item pool of 32 items was finalized through statistical evaluation. Subsequently, this scale was administered to 355 individuals of the Gujrat district. Statistical analysis was applied for the confirmation of data such as exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Moreover, Cronbach alpha reliability test signified the reliability of this scale. Results: EFA directed to four factors possessing 80 items. Furthermore, CFA was executed, and the model fit summary presented good range values such as (GFI=0.886, CFI=0.901, RMSEA= 0.41, RMR=0.45) after the removal of 48 items with significance p-value (0.001). The reliability was reported 0.932. Conclusion: A standard scale to measure assertiveness level in adults was successfully constructed with 32 items.